(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Army of the Sultanate consisted with the regular and irregular troops of the Sultans, Wali, Muqti and nobles. The Sultanate army had lost soldiers war-horses and war elephants in constant warfare. Consequently, the Sultans compelled to employ new soldiers, war horses and elephants in their army. They generally held muster once in a year and periodically during the wars in order to maintain discipline in the army. They trained their soldiers though military and hunting expeditions. We shall now discuss in this chapter military personnel or composition, recruitment, muster and training.